2016
DOI: 10.1074/jbc.m116.720789
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian α-1,6-Fucosyltransferase (FUT8) Is the Sole Enzyme Responsible for the N-Acetylglucosaminyltransferase I-independent Core Fucosylation of High-mannose N-Glycans

Abstract: Understanding the biosynthetic pathway of protein glycosylation in various expression cell lines is important for controlling and modulating the glycosylation profiles of recombinant glycoproteins. We found that expression of erythropoietin (EPO) in a HEK293S N-acetylglucosaminyltransferase I (GnT I) ؊/؊ cell line resulted in production of the Man 5 GlcNAc 2 glycoforms, in which more than 50% were core-fucosylated, implicating a clear GnT I-independent core fucosylation pathway. Expression of GM-CSF and the ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
75
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 31 publications
4
75
0
Order By: Relevance
“…Recently, we observed unexpected high corefucosylation of Man5GlcNAc2 (M5) glycan (more than 50%) of EPO produced from a HEK293S GnTI knockout cell line 33 . To characterize the underlying mechanism and to increase the fucosylation level of EPO-M5 as a potential starting material for glycan remodeling, we have generated a 293S GnTĪFUT8↑ cell line by lentiviral-mediated gene transfer, and found that expression of EPO from this cell line yielded almost 100% homogenous M5F glycan 33 . This successful generation of this unusual glycoform prompted us to explore it to obtain the Fucα1,6GlcNAc-EPO as the key precursor for EPO glycan remodeling.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, we observed unexpected high corefucosylation of Man5GlcNAc2 (M5) glycan (more than 50%) of EPO produced from a HEK293S GnTI knockout cell line 33 . To characterize the underlying mechanism and to increase the fucosylation level of EPO-M5 as a potential starting material for glycan remodeling, we have generated a 293S GnTĪFUT8↑ cell line by lentiviral-mediated gene transfer, and found that expression of EPO from this cell line yielded almost 100% homogenous M5F glycan 33 . This successful generation of this unusual glycoform prompted us to explore it to obtain the Fucα1,6GlcNAc-EPO as the key precursor for EPO glycan remodeling.…”
Section: Resultsmentioning
confidence: 99%
“…The cells were passaged every 3-4 days with the initial seeding density of 3 ×10 5 cells per ml. The culture of HEK293S GnTĪFUT8↑followed the procedures previously reported by Yang et al 33 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In animals and humans, core-fucosylation is catalyzed solely by the mammalian α1,6-fucosyltransferase, FUT8 27,28 . However, FUT8 has a very strict substrate specificity, requires the presence of a free GlcNAc at the α1,3-linked mannose arm in the N-glycan as the substrate and usually is unable to fucosylate full-size mature N-glycans 2932 .…”
Section: Introductionmentioning
confidence: 99%